Renewable Energy and Economic Stability: A Study of How Solar Power is Transforming Local Economies in Sub-Saharan Africa - Gbenga Joseph Ayeni, Gbenga Joseph Ayeni (African Journal of Stability and Development (AJSD), 2025)
This study examines how solar energy is transforming local economies in Sub-Saharan Africa, with a focus on how it can reduce energy poverty and foster economic stability. Solar power, an abundant and renewable resource, is increasingly being used to address the region’s energy issues. However, despite the potential benefits, barriers to widespread solar adoption include inadequate infrastructure, financing challenges, and regulatory constraints. The study illustrates how solar energy is enhancing energy access, generating employment, and promoting entrepreneurship. The study is done using case studies from Kenya, Rwanda, Nigeria, and South Africa. Critical challenges to solar expansion are also identified in the study, such as high upfront costs, a lack of technical know-how, and a lack of policy support. It recommends a comprehensive strategy to hasten the adoption of solar energy that includes technical capacity building, private sector involvement, and government interventions. If these barriers are removed, solar energy has the potential to significantly contribute to Sub-Saharan Africa’s inclusive economic growth, poverty alleviation, and sustainable development.